Phytochemistry and Biological Activities of the Genus Knema (Myristicaceae) - Wan Mohd Nuzul Hakimi Wan Salleh*, Farediah Ahmad (Tabriz University of Medical Sciences, 2017)
Knema, a genus of the family Myristicaceae, usually found in Southeast Asia, has been used to treat sores, pimples, rheumatism, and cancer. A compilation of the research on isolation, structure elucidation, structural diversity, and bioactivities of Knema secondary metabolites reported between 1978 and 2016 are included in this review. Up to now, the reported constituents from the genus Knema included acetophenone, substituted stilbene, lignan, flavonoid, alkyl/acyl resorcinol, and phenylalkylphenol derivatives. Studies showed that Knema and its active principles possessed a wide range of biological activities such as antibacterial, antinematodal, anti-inflammatory, cytotoxicity, and acetylcholinesterase inhibitory activities. The increasing amounts of data support the application and exploitation for new drug development.